2706 km cycling in 2 weeks: effects on cardiac function in 6 elderly male athletes. Issue 3 (3rd July 2018) - Morville, Thomas; Rosenkilde, Mads; Mattsson, Nick; Dela, Flemming; Helge, Jørn W; Rasmusen, Hanne K
ABSTRACT: Objectives : Physiological effects of exercise on trained and untrained individuals have been studied extensively. Typically, young or middle-aged individuals are examined before and after short periods of vigorous exertion. Methods : We studied 6 elderly male athletes (61 ± 8 years (mean ± SD); baseline O2 max 48 ± 5 ml·kg −1 ·min −1 ) with focus on cardiac function and biomarkers following 14 consecutive days of moderate intensity exercise. Cardiac dimensions, function, biomarkers, and other measures of cardiovascular health were examined at baseline and 2 and 28 h after the last day of cycling a total of 2706 km. Results : Data collected after the cessation of exercise on the 14th day revealed significant increases in average size of the left atrium (3.5 ± 0.4 to 4.0 ± 0.3 cm; p  = 0.02) and left ventricular end systolic volume (47 ± 2 to 52 ± 5 ml; p  = 0.004), with no other significant changes in cardiac size or function. Small, transient increases in cardiac biomarkers (troponin T, creatine kinase myocardial band, and N-terminal pro-brain natriuretic peptide) ( p  < 0.01) were observed 2 h after completion of cycling but no changes in systolic (including strain-analyses) or diastolic cardiac function were observed at rest. O2 max was significantly lower at the 28 h time point than at baseline ( p  < 0.02). Plasma concentrations of total- ( p  < 0.01) and low-density lipoprotein-cholesterol ( p  < 0.01) were markedly lower after exercise. Systolic blood pressure was unchanged, but diastolic pressure was significantly lower after exercise than at baseline. Conclusions : The results suggest that repeated moderate intensity exercise in elderly men was associated with a transient increase in cardiac biomarkers while cardiac function remained unaltered. A favorable reduction in blood lipids and diastolic blood pressure were seen for >28 h after the end of activity. An unexplained symptomless severe plasma hyponatremia developed in 3 of 6 subjects 28 h after the end of activity.